Evaluation of radiopacity of cements used in implant-supported prosthesis by indirect digital radiography: an in-vitro study - Mahla Esfahanian; Amin Mahdavi Asl (European Journal of Translational Myology, 2023)
In order to help dentists in choosing the right type of cement for implant-based prostheses, the radiopacity of commonly used cements available in the market was investigated by digital radiography with PSP sensor. In the present study, temporary cements of TempBond (Kerr, Germany), TempBond clear (Kerr, Germany), Dycal (Dentsply, USA) and permanent cements of Multilink N (Ivoclar, Brazil), Panavia F 2.0 (Kurrary, Japan), Fuji plus (GC, Japan), RelyX (3M, USA), Durelon (3M, USA) were used. Four pill-like samples with 0.5 mm and 1 mm thickness and 5 mm in diameter inside the silicon index as recommended by the manufacturer were prepared for each cement. Aluminum step wedge (99% aluminum alloy) was used as control. Using digital radiography, cement and aluminum step wedge samples were radiographed. The images of cement tablets were measured by digital radiography using DFW software to check their radiopacity values. Bonferroni test and Mann-Whitney U test were used for comparison of cements. The highest radiopacity between the group of 1 and 0.5 mm thickness was related to Glass ionomer Fujiplus GC (2407±45.99) and TempBond (137.21±22.46) cement, respectively. Whereas, the lowest radiopacity among the groups was related to Clear cement. The difference between the mean radiopacities among the studied groups was statistically significant (p<0.001). Based on the results, among the available cements, Glass ionomer Fujiplus GC and TempBond cement are the most efficient for 1 and 0.5 mm thickness, respectively, and Clear cement is the least efficient cement in both groups in terms of radiopacity.